Anthropometric assessment and oral microbiota of preschoolers in the city of Taubaté-SP through a cross-sectional observational study (Research, Society and Development, 2025)
Introduction: Anthropometric evaluation and oral microbiota are important indicators of quality of life from early childhood. Objective: To describe the anthropometry and composition of the oral microbiota of preschool children from public and private schools in the city of Taubaté-SP. Methods: A cross-sectional observational study was conducted using anthropometric data: weight, height, circumferences, skinfolds, and calculating the anthropometric indices recommended by the World Health Organization (WHO, 2006) for preschoolers, aged four years, in the city of Taubaté in 2023. The oral microbiota was analyzed by polymerase chain reaction of saliva samples. Results: The BMI of 351 preschoolers, 173 from public schools and 178 from private schools, revealed: underweight in 1.4% (95% CI: 0.3 to 1.5); normal weight in 75.1% (95% CI: 70.1 to 79.5); risk of overweight in 14.4% (95% CI: 14.1 to 18.9); overweight in 6.8% (95% CI: 4.2 to 7.3); and obesity in 2.3% (95% CI: 3.2 to 5.9). Total bacterial load was higher in preschoolers from public schools, with a predominance of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, while the predominant bacterium in preschoolers from private schools was Streptococcus oralis. Conclusions: The CC/E ratio was a sensitive anthropometric index in differentiating groups, showing a strong association with overweight. The bacterial disparity found between the groups highlights the importance of specific interventions to promote oral health in different social contexts.